Copolyester resin and method for producing same

By combining biodegradable and non-biodegradable segments in the copolyester resin to form block copolymers, the problem of insufficient thermoformability and biodegradability of existing copolyester resins at high temperatures is solved. Efficient biodegradation and thermoformability in a variety of environments are achieved.

CN119213053APending Publication Date: 2024-12-27DIC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040681.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-13
Filing Date
2023-05-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing copolyester resins have limited molecular weight in seawater dependent on the polylactic acid site, and are difficult to thermoform at high temperatures, affecting their thermoforming and biodegradability.

Method used

Design a copolyester resin, which is composed of a biodegradable chain segment and abiotic-degradable chain segment. The biodegradable chain segment is derived from a structure bonded by hydroxyalkanoic acid or dibasic acid and diol, and is abiotic-degradable. The sexual segments are derived from butylene succinate or adipic acid/butylene terephthalate, and block copolymers are formed through transesterification reactions to ensure that biodegradability and thermoformability are maintained at high temperatures.

Benefits of technology

It realizes excellent biodegradability in seawater, freshwater, soil and compost environments, and maintains excellent thermoforming properties at high temperatures, solving the shortcomings of thermoforming and biodegradability of copolyester resins in the prior art. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005135774420000031
    Figure BDA0005135774420000031
  • Figure BDA0005135774420000032
    Figure BDA0005135774420000032
  • Figure BDA0005135774420000041
    Figure BDA0005135774420000041
Patent Text Reader

Abstract

Provided are: a copolyester resin having excellent thermoformability and biodegradability; and a method for producing the copolyester resin. A copolyester resin obtained by combining a biodegradable segment (X), which is a structural unit exhibiting biodegradability, and a non-biodegradable segment (Y), which is a structural unit having non-biodegradability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copolyester resin and a preparation method thereof. Background Art

[0002] Most synthetic resins cannot be easily decomposed in the natural environment. Therefore, synthetic resins cause problems of environmental degradation. For example, discarded synthetic resins become microplastics that pollute the marine environment.

[0003] In response to the social issue of global environmental degradation caused by the massive disposal of synthetic resins, there is an increasing need for sustainable product groups (packaging materials, films, etc.) using resins that are biodegradable in all environments (seawater, fresh water, soil, compost, etc.).

[0004] Examples of resins that are biodegradable in all environments include polyhydroxyalkanoates (PHA). PHA has attracted attention as a resin that is friendly to the natural environment, and has been widely used, and is expected to expand its application areas in the future.

[0005] However, the melting temperature and thermal decomposition temperature of PHA are close to each other, and the low thermoformability of general-purpose resins becomes a problem in order to perform thermal decomposition during processing. In addition, when synthesizing PHA polymers from monomers by chemical polymerization, it is difficult to synthesize high molecular weight bodies due to the low upper limit of the polymerization temperature. Therefore, biodegradable resins that can be polymerized at relatively high temperatures like general-purpose resins and can be thermoformed are required.

[0006] In order to solve the above problems, a technology has been reported that introduces a specific chemical structure into polyester in which the environment in which the biodegradability is limited so as to make the polyester biodegradable in other environments. For example, non-patent documents 1 and 2 report copolyester resins having seawater biodegradability and thermal properties.

[0007] Prior art literature

[0008] Non-patent literature

[0009] Non-patent literature 1: Polymer Degradation and Stability, 181, (2020), 109353

[0010] Non-patent document 2: Polymer Degradation and Stability, 184, (2021), 109467 Summary of the invention

[0011] Problem that the invention aims to solve

[0012] However, the copolyester resins disclosed in Non-Patent Documents 1 and 2 are triblock copolymers, so the seawater biodegradability of the copolyester resin depends on the molecular weight of the polylactic acid portion, which is a non-seawater degradable portion. Therefore, there is a limit on the molecular weight in the design of the copolyester resin. In addition, it is required to further improve the thermoformability and biodegradability.

[0013] Therefore, an object of the present invention is to provide a copolyester resin having excellent thermoformability and biodegradability and a method for producing the same.

[0014] Solutions for solving problems

[0015] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that the above-mentioned problems can be solved, and have completed the present invention having the following gist.

[0016] That is, the present invention includes the following aspects.

[0017] [1] A copolyester resin comprising a biodegradable segment (X) and a non-biodegradable segment (Y), wherein the biodegradable segment (X) is a structural unit exhibiting biodegradability and the non-biodegradable segment (Y) is a structural unit having non-biodegradability.

[0018] [2] The copolyester resin according to [1], wherein the molar ratio (X / Y) of the biodegradable segment (X) to the non-biodegradable segment (Y) is 1 / 99 to 95 / 5.

[0019] [3] The copolyester resin according to [1] or [2], wherein the biodegradable segment (X) is a biodegradable segment (X) derived from a polymer (x), wherein the polymer (x) contains a biodegradable structural unit derived from a hydroxyalkanoic acid or from a structure in which a dibasic acid (Ia) and a diol (Ib) are bonded.

[0020] [4] The copolyester resin according to any one of [1] to [3], wherein the non-biodegradable segment (Y) is a non-biodegradable segment (Y) derived from a polymer (y) containing a non-biodegradable structural unit.

[0021] [5] The copolyester resin according to any one of [1] to [4], wherein the average chain length of the biodegradable segment (X) is greater than 1.2.

[0022] [6] The copolyester resin according to any one of [3] to [5], wherein the hydroxyalkanoic acid is a structural unit derived from 6-hydroxycaproic acid or a structural unit derived from polycaprolactone.

[0023] [7] The copolyester resin according to any one of [3] to [6], wherein the dibasic acid (Ia) is represented by formula (1) and the diol (Ib) is represented by formula (2).

[0024]

[0025] (In formula (1), n ​​represents an integer of 4 to 8.)

[0026]

[0027] (In formula (2), A represents a carbon atom or an oxygen atom, R 1 represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a hydroxyl group, and R 2 represents a hydrogen atom or a hydroxyl group. l and m are each independently an integer of 0 to 4, and l+m represents 1 or more.

[0028] When A is an oxygen atom, R does not exist. 1 and H bonded to A. In addition, R 1 and R 2 Any one of them is hydroxyl, R 1 and R 2 Not all are hydroxyl groups.)

[0029] [8] The copolyester resin according to any one of [3] to [7], wherein the biodegradable structural unit in the polymer (x) is represented by the following formula (3A) or (3B).

[0030]

[0031] (In formula (3A) and formula (3B), R 3 represents a hydrogen atom or a methyl group, l and m are each independently an integer of 0 to 4, l+m is 1 or more, and n represents an integer of 4 to 8.

[0032] [9] The copolyester resin according to any one of [3] to [8], wherein the dibasic acid (Ia) is at least one selected from the group consisting of adipic acid, azelaic acid, and sebacic acid.

[0033]

[10] The copolyester resin according to any one of [3] to [9], wherein the diol (Ib) is at least one selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol and 1,9-nonanediol.

[0034]

[11] The copolyester resin according to any one of [3] to

[10] , wherein the structural unit exhibiting biodegradability in the polymer (x) is at least one selected from the group consisting of the following structural units:

[0035] A structural unit derived from a structure in which ethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which diethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and adipic acid are bonded,

[0036] A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which diethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and sebacic acid are bonded,

[0037] A structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol and adipic acid are bonded together; a structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, 2-methyl-1,3-propanediol and adipic acid are bonded together;

[0038] A structural unit derived from a structure in which ethylene glycol, diethylene glycol and adipic acid are bonded together; a structural unit derived from a structure in which ethylene glycol, diethylene glycol, 2-methyl-1,3-propanediol and adipic acid are bonded together;

[0039] A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded together, and a structural unit derived from a structure in which ethylene glycol, 2-methyl-1,3-propanediol, adipic acid, and sebacic acid are bonded together.

[0040]

[12] The copolyester resin according to any one of [4] to

[11] , wherein the non-biodegradable structural unit in the polymer (y) is derived from butylene succinate or butylene adipate terephthalate.

[0041]

[13] The copolyester resin according to any one of [4] to

[12] , wherein the non-biodegradable structural unit in the polymer (y) is:

[0042] Any of a structural unit derived from a structure in which 1,4-butanediol and succinic acid are bonded together, and a structural unit derived from a structure in which 1,4-butanediol, adipic acid, and terephthalic acid are bonded together.

[0043]

[14] The copolyester resin according to any one of [1] to

[13] , wherein the biodegradable structural unit, i.e., the biodegradable segment (X), comprises a unit (A) and a unit (B), and the unit (A) and the unit (B) are any one of the following segments (i) to (iii).

[0044] (i)

[0045] The aforementioned unit (A) is a triad unit derived from "a structure in which 2-methyl-1,3-propanediol, adipic acid and 2-methyl-1,3-propanediol are bonded together", and the aforementioned unit (B) is a triad unit derived from "a structure in which 1,4-butanediol, adipic acid and 1,4-butanediol are bonded together",

[0046] (ii)

[0047] The aforementioned unit (A) is a triad unit derived from "a structure in which 2-methyl-1,3-propanediol, sebacic acid and 2-methyl-1,3-propanediol are bonded together", and the aforementioned unit (B) is a triad unit derived from "a structure in which 1,4-butanediol, sebacic acid and 1,4-butanediol are bonded together", or

[0048] (iii)

[0049] The unit (A) is a triad unit derived from "a structure in which 3-methyl-1,5-pentanediol, adipic acid and 3-methyl-1,5-pentanediol are bonded together", and the unit (B) is a triad unit derived from "a structure in which 1,4-butanediol, adipic acid and 1,4-butanediol are bonded together".

[0050]

[15] The copolyester resin according to any one of [1] to

[14] , wherein the melting point (Tm) of the copolyester resin is 65° C. or higher.

[0051]

[16] The copolyester resin according to any one of [1] to

[15] , wherein the copolyester resin is biodegradable in a seawater environment, a freshwater environment, a soil environment, and a compost environment.

[0052]

[17] A method for producing a copolyester resin, which is a method for producing the copolyester resin described in any one of [1] to

[16] , which is a method for producing a copolyester resin composed of a biodegradable segment (X) and a non-biodegradable segment (Y).

[0053] The aforementioned biodegradable segment (X) is a segment derived from a polymer (x), wherein the polymer (x) contains a biodegradable structural unit.

[0054] The non-biodegradable segment (Y) is a segment derived from a polymer (y), wherein the polymer (y) contains a non-biodegradable structural unit.

[0055] The production method comprises the step of subjecting the polymer (x) and the polymer (y) to an ester exchange reaction to obtain a block copolymer comprising the biodegradable segment (X) and the non-biodegradable segment (Y).

[0056]

[18] A resin composition comprising the copolyester resin according to any one of [1] to

[16] .

[0057]

[19] A sheet or a film formed from the resin composition according to

[18] .

[0058] Effects of the Invention

[0059] According to the present invention, a copolyester resin having excellent thermoformability and biodegradability and a method for producing the same can be provided. DETAILED DESCRIPTION

[0060] Hereinafter, the copolyester resin of the present invention will be described in detail. The description of the technical features described below is an example as one embodiment of the present invention, and the present invention is not limited to these contents.

[0061] (Copolyester resin)

[0062] The copolyester resin of the present invention is a resin composed of a biodegradable segment (X) and a non-biodegradable segment (Y), wherein the biodegradable segment (X) is a structural unit exhibiting biodegradability and the non-biodegradable segment (Y) is a structural unit having non-biodegradability.

[0063] A substance "has biodegradability" means, for example, that when discharged into the natural environment, the substance is decomposed into carbon dioxide and water by the action of microorganisms, etc. Examples of the "environment" to be decomposed include seawater environment, freshwater environment, soil environment, and compost.

[0064] However, in the present invention, particular attention is paid to biodegradability in seawater environments.

[0065] In the present invention, "exhibiting biodegradability" means that the degradation rate in seawater is 15% or more.

[0066] On the other hand, in the present invention, "exhibiting non-biodegradability" means that the degradation rate in seawater is less than 15%.

[0067] It should be noted that, in the present invention, the degradability for "seawater environment" is specified, but environments other than seawater environment are not excluded from the object. It is further preferred that the biodegradability is not only exhibited in the seawater environment, but also the degradation rate is shown to be 15% or more in each environment other than the seawater environment, such as freshwater environment, soil environment, or compost.

[0068] The copolyester resin of the present invention has excellent biodegradability and can be polymerized and thermoformed at a relatively high temperature as that of general-purpose resins. That is, the copolyester resin of the present invention has excellent thermoformability and biodegradability. In addition, a sheet, a film, etc. using a resin composition containing the copolyester resin can be obtained.

[0069] An example of the presumed mechanism of action by which excellent thermoformability and biodegradability effects can be significantly obtained is shown below.

[0070] In the copolyester resin of the present invention, a biodegradable segment (X) and a non-biodegradable segment (Y) exist in combination, wherein the biodegradable segment (X) is a structural unit showing biodegradability, and the non-biodegradable segment (Y) is a structural unit having non-biodegradability. The segment (X) is cut by enzymes in the environment. Thus, the copolyester resin becomes an oligomer that can be metabolized by microorganisms, and the copolyester resin as a whole is biodegraded. Furthermore, the copolyester resin of the present invention contains a segment (Y) having a structural unit, and the structural unit shows non-biodegradability with excellent thermoformability. Thus, the copolyester resin as a whole has excellent thermoformability.

[0071] In addition to the above characteristics, the copolyester resin of the present invention also contains a variety of biodegradable structural units in a well-balanced manner at respective prescribed ratios, and the enzymes in the environment can ensure that the biodegradable sites are cut at multiple locations, thereby promoting the biodegradability of the entire copolyester resin.

[0072] To explain in more detail, for example, the copolyester resin of the present invention contains a segment (X) derived from a polymer (x), wherein the polymer (x) has a structural unit showing biodegradability, and the structural unit is derived from a hydroxyalkanoic acid, or from a structure formed by bonding a dibasic acid (Ia) and a diol (Ib). The segment (X) is cleaved by an enzyme in the environment. As a result, the copolyester resin becomes an oligomer that can be metabolized by microorganisms, and the copolyester resin as a whole is biodegradable. Furthermore, the copolyester resin of the present invention contains a segment (Y) derived from a polymer (y), wherein the polymer (y) has a structural unit showing non-biodegradability with excellent thermoformability. As a result, the copolyester resin as a whole has excellent thermoformability.

[0073] Since the copolyester resin is formed by containing the biodegradable segment (X) and the non-biodegradable segment (Y) at a specific mixing ratio, the biodegradable segment (X) present at a specific ratio is cleaved, thereby the copolyester resin becomes an oligomer that can be metabolized by microorganisms, and the copolyester resin as a whole is biodegraded. Furthermore, since the non-biodegradable segment (Y) in the copolyester resin of the present invention is present at a specific ratio, the copolyester resin as a whole has excellent thermoformability.

[0074] Furthermore, if the biodegradable segments (X) derived from the polymer (x) are arranged in a specific average chain length in the copolyester resin, the biodegradable segments (X) having the specific average chain length are cleaved by enzymes in the environment, so that the copolyester resin becomes an oligomer that can be metabolized by microorganisms, and the copolyester resin as a whole is biodegraded. Furthermore, the copolyester resin of the present invention contains a non-biodegradable structural unit with excellent thermoformability, and the non-biodegradable segments (Y) derived from the polymer (y) are arranged in a specific molar ratio, so that the copolyester resin as a whole has excellent thermoformability.

[0075] Hereinafter, the structural components of the copolyester resin will be described.

[0076] The copolyester resin comprises a biodegradable segment (X) and a non-biodegradable segment (Y), and more preferably comprises an appropriate combination of these biodegradable segment (X) and non-biodegradable segment (Y).

[0077] Furthermore, the copolyester resin comprises a biodegradable segment (X) derived from a polymer (x) containing a biodegradable structural unit and a non-biodegradable segment (Y) derived from a polymer (y) containing a non-biodegradable structural unit.

[0078] The polymer (x) is preferably a polymer containing a biodegradable structural unit derived from a hydroxyalkanoic acid or a structure in which a dibasic acid (Ia) and a diol (Ib) are bonded to each other.

[0079] On the other hand, the polymer (y) is a polymer containing a non-biodegradable structural unit, and preferably is a polymer containing a non-biodegradable structural unit derived from a structure in which a dibasic acid and a diol are bonded, for example.

[0080] <Polymer (x) containing a biodegradable structural unit>

[0081] The polymer (x) contains at least one biodegradable structural unit. The biodegradable structural unit contained in the polymer (x) may be one kind or a combination of two or more kinds.

[0082] The structural unit contained in the polymer (x) is preferably derived from a hydroxyalkanoic acid or a structure in which a dibasic acid (Ia) and a diol (Ib) are bonded to each other.

[0083] Examples of the hydroxyalkanoic acid or dibasic acid (Ia) and diol (Ib) for forming the polymer (x) include the following compounds.

[0084] The seawater degradation rate of the structure obtained by bonding varies depending on the combination of the types of hydroxyalkanoic acid, dibasic acid and diol. Therefore, in forming the biodegradable polymer (x), it is advisable to appropriately select preferred types from among the hydroxyalkanoic acids, dibasic acids and diols exemplified below so that the structure when bonded shows a seawater degradation rate of 15% or more.

[0085] <<Hydroxyalkanoic acid>>

[0086] Examples of hydroxyalkanoic acid include glycolic acid, 2-hydroxypropionic acid (lactic acid), 3-hydroxypropionic acid, 2-hydroxybutyric acid (2-hydroxybutyric acid), 3-hydroxybutyric acid, 4-hydroxybutyric acid, 3-hydroxy-3-methyl-butyric acid, 2-hydroxyvaleric acid (2-hydroxyvaleric acid), 3-hydroxyvaleric acid, 5-hydroxyvaleric acid, 2-hydroxy-2-methyl-valeric acid, 3-hydroxyhexanoic acid, 6-hydroxyhexanoic acid, 6-hydroxyheptanoic acid, 3-hydroxyheptanoic acid, 7-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 8-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 9-hydroxynonanoic acid, 3-hydroxydecanoic acid, and 10-hydroxydecanoic acid. 1-6 Alkyl hydroxyl C 2-15 Alkane acid, 12-hydroxystearic acid, ricinoleic acid and other units.

[0087] It should be noted that the unit of hydroxyalkanoic acid may also be a unit of the corresponding lactone. Examples of the lactone unit include: β-propiolactone, β-dimethylpropiolactone, γ-butyrolactone, γ-dimethylbutyrolactone, δ-valerolactone, ε-caprolactone, and other units having di-C 1-12 Alkyl C 3-15 Lactone and other units.

[0088] The units of these hydroxyalkanoic acids and lactones may be used alone or in combination of two or more. Among these hydroxyalkanoic acid units, 3-hydroxypropionic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid (4-hydroxybutyric acid), 3-hydroxyvaleric acid, 3-hydroxyhexanoic acid, 6-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, 10-hydroxydecanoic acid and the like are preferred from the viewpoint of biodegradability. 3-10 Alkyl acid units (except 3-hydroxybutyric acid) 3-10 units of alkanoic acid) or units of the corresponding lactone.

[0089] The hydroxyalkanoic acid is preferably a structural unit derived from 6-hydroxycaproic acid or a structural unit derived from polycaprolactone.

[0090] Here, poly(caprolactone) is a polyester represented by the following formula (t).

[0091]

[0092] (In formula (t), a represents a positive integer.)

[0093] Poly(caprolactone) is a ring-opening reaction product of ε-caprolactone. The structural unit of poly(caprolactone) is a structural unit (6HH-U) derived from 6-hydroxycaproic acid (6HH).

[0094] The structural unit of poly(caprolactone) refers to one residue of 6-hydroxycaproic acid (6HH) in the copolyester, specifically, a structure in which a hydrogen atom in a hydroxyl group and a hydroxyl residue in a carboxyl group of 6-hydroxycaproic acid (6HH) are removed.

[0095] <<Dibasic Acid>>

[0096] The dibasic acid is not particularly limited, and examples thereof include non-aromatic dicarboxylic acids, aromatic dicarboxylic acids, anhydrides thereof, halides thereof, and esters thereof.

[0097] <<<Non-aromatic dicarboxylic acids>>>

[0098] Examples of the non-aromatic dicarboxylic acid include aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, and unsaturated bond-containing non-aromatic dicarboxylic acids. The number of carbon atoms in the non-aromatic dicarboxylic acid is not particularly limited, and is, for example, 3 to 15.

[0099] Examples of the aliphatic dicarboxylic acid include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid.

[0100] Examples of the alicyclic dicarboxylic acid include alicyclic dicarboxylic acids having 8 to 15 carbon atoms.

[0101] As an alicyclic dicarboxylic acid, 1, 3- cyclopentane dicarboxylic acid, 1, 4- cyclohexane dicarboxylic acid, etc. are mentioned, for example.

[0102] Examples of the unsaturated bond-containing non-aromatic dicarboxylic acid include maleic acid and fumaric acid.

[0103] <<<Aromatic dicarboxylic acids>>>

[0104] Examples of the aromatic dicarboxylic acid include aromatic dicarboxylic acids having 6 to 20 carbon atoms. More specifically, examples of the aromatic dicarboxylic acid include phthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, and 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid.

[0105] Among these dibasic acids, non-aromatic dicarboxylic acids are preferred from the viewpoint of biodegradability, aliphatic dicarboxylic acids are more preferred, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid represented by the following formula (1) are further preferred, adipic acid, azelaic acid, and sebacic acid are further preferred, and adipic acid and sebacic acid are particularly preferred. Two or more dibasic acids may be used in combination.

[0106]

[0107] (In formula (1), n ​​represents an integer of 4 to 8.)

[0108] <<Diol>>

[0109] Examples of the diol include non-aromatic diols and aromatic diols.

[0110] <<<Non-aromatic diols>>>

[0111] Examples of the non-aromatic diol include aliphatic diols and alicyclic diols. Examples of the carbon number of the non-aromatic diol include 1 to 15 carbon atoms.

[0112] Examples of the aliphatic diol include ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, neopentyl glycol, cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2-methyl-2,4-pentanediol, 3,3-dimethyl-1,2-butanediol, 2,3-dimethyl-2,3-butanediol, butylethylpropylene glycol, 1,9-nonanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol.

[0113] Examples of the alicyclic diol include alicyclic diols having 6 to 15 carbon atoms, and examples of the alicyclic diol include 1,3-bis(2-hydroxypropyl)cyclopentane, 1,3-bis(2-hydroxybutyl)cyclopentane, 1,4-bis(hydroxymethyl)cyclohexane, 1,4-bis(2-hydroxypropyl)cyclohexane, and 1,4-bis(2-hydroxybutyl)cyclohexane.

[0114] Examples of the aromatic diol include aromatic diols having 6 to 20 carbon atoms.

[0115] Examples of the aromatic diol having 6 to 20 carbon atoms include isophthalic acid alcohol, p-phthalic acid alcohol, 1,4-phenylenediethanol, and 1,4-bis(2-hydroxyethoxy)benzene.

[0116] Among these diols, non-aromatic diols are preferred from the viewpoint of biodegradability, aliphatic diols are more preferred, and diols represented by the following formula (2) are particularly preferred. Two or more diols may be used in combination.

[0117]

[0118] (In formula (2), A represents a carbon atom or an oxygen atom, R 1 represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a hydroxyl group, and R 2 represents a hydrogen atom or a hydroxyl group. l and m are each independently an integer of 0 to 4, and l+m represents 1 or more.

[0119] However, when A is an oxygen atom, R does not exist. 1 and H bonded to A. In addition, R 1 and R 2 Any one of them is a hydroxyl group, R 1 and R 2 Not all are hydroxyl groups.)

[0120] Examples of the alkyl group having 1 to 4 carbon atoms include methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, 1-methyl-cyclopropyl, and 2-methyl-cyclopropyl. Among these, a methyl group is preferred because of its excellent reactivity.

[0121] Among the diols represented by formula (2), 1,3-propanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-(2-hydroxyethoxy)ethanol, and 3-(3-hydroxypropoxy)-1-propanol are preferred. From the viewpoint of excellent biodegradability, 2-methyl-1,3-propanediol and 3-methyl-1,5-pentanediol are more preferred.

[0122] The structural unit having biodegradability is derived from a structure obtained by arbitrarily selecting the above-mentioned dibasic acid and the above-mentioned diol and subjecting them to an esterification reaction by a known method.

[0123] Although not particularly limited, a suitable example of the biodegradable structural unit includes a structural unit represented by the following formula (3A) or the following formula (3B).

[0124]

[0125] (In formula (3A) and formula (3B), R 3 represents a hydrogen atom or a methyl group, l and m are each independently an integer of 0 to 4, l+m is 1 or more, and n represents an integer of 4 to 8.

[0126] In formula (3A), R 3 It is preferably a methyl group, l and m are each independently an integer of 1 or 2, and n is an integer of 4 to 8.

[0127] In forming the biodegradable polymer (x), among the dibasic acids exemplified above, the dibasic acid (Ia) described below is preferably used.

[0128] The dibasic acid (Ia) forming the biodegradable polymer (x) is preferably at least one selected from the group consisting of adipic acid, azelaic acid, and sebacic acid.

[0129] Furthermore, in forming the biodegradable polymer (x), among the diols exemplified above, the diol (Ib) described below is preferably used.

[0130] The diol (Ib) forming the biodegradable polymer (x) is preferably at least one selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol.

[0131] The structural unit exhibiting biodegradability in the polymer (x) is preferably at least one selected from the group consisting of the following structural units:

[0132] A structural unit derived from a structure in which ethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which diethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and adipic acid are bonded,

[0133] A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which diethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and sebacic acid are bonded,

[0134] A structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol and adipic acid are bonded together; a structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, 2-methyl-1,3-propanediol and adipic acid are bonded together;

[0135] A structural unit derived from a structure in which ethylene glycol, diethylene glycol and adipic acid are bonded together; a structural unit derived from a structure in which ethylene glycol, diethylene glycol, 2-methyl-1,3-propanediol and adipic acid are bonded together;

[0136] A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded together, and a structural unit derived from a structure in which ethylene glycol, 2-methyl-1,3-propanediol, adipic acid, and sebacic acid are bonded together.

[0137] Among them, the structural unit exhibiting biodegradability in the polymer (x) is more preferably:

[0138] Any of a structural unit derived from a structure in which 2-methyl-1,3-propanediol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and sebacic acid are bonded, and a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded.

[0139] When described as a specific structural formula, for example, structural units represented by the following formulae (3-1) to (3-3) and the like are exemplified.

[0140]

[0141]

[0142] <Polymer (y) containing a non-biodegradable structural unit>

[0143] The polymer (y) contains a non-biodegradable structural unit. The non-biodegradable structural unit contained in the polymer (y) may be used alone or in combination of two or more.

[0144] The non-biodegradable structural unit is not particularly limited as long as it is non-biodegradable and can form a copolymer with a biodegradable structural unit.

[0145] Examples of the dibasic acid and diol used for forming the polymer (y) include the dibasic acids and diols described in the above section "Polymer (x) having a structural unit exhibiting biodegradability".

[0146] The seawater degradation rate of the structure obtained by bonding varies depending on the combination of the type of dibasic acid and the type of diol. Therefore, in forming the polymer (y) showing non-biodegradability, it is advisable to appropriately select preferred types from the dibasic acids and diols exemplified above so that the structure when bonded shows a seawater degradation rate of less than 15%.

[0147] The non-biodegradable structural unit is not particularly limited, but preferably contains a structural unit derived from a structure in which a dibasic acid other than the dibasic acid represented by the above formula (1) described in the column of <Polymer (x) having a biodegradable structural unit> is bonded to a diol.

[0148] The non-biodegradable structural unit is not particularly limited, and examples thereof include structural units derived from butylene succinate, adipic acid / butylene terephthalate, etc. Among these, the non-biodegradable structural unit in the polymer (y) is preferably any one of a structural unit derived from butylene succinate represented by the following formula (4-1) (corresponding to a structural unit derived from a structure formed by bonding 1,4-butanediol and succinic acid), and a structural unit derived from adipic acid / butylene terephthalate represented by the following formula (4-2) (a structural unit derived from a structure formed by bonding 1,4-butanediol, adipic acid, and terephthalic acid).

[0149]

[0150] <Any polymer containing other structural units>

[0151] The copolyester resin of the present invention may contain any polymer having other structural units than those described above as necessary within a range not inhibiting the effects of the present invention.

[0152] The copolyester resin of the present invention is a block copolymer comprising a biodegradable segment (X) and a non-biodegradable segment (Y), and is obtained by copolymerizing a polymer (x) containing the above-mentioned biodegradable structural unit and a polymer (y) containing the above-mentioned non-biodegradable structural unit.

[0153] Although not particularly limited, preferred examples of the copolyester resin of the present invention include the following formulas (5) to (8).

[0154]

[0155] (In formula (5), o, p, and q each independently represent a positive integer.)

[0156]

[0157] (In formula (6), o, p, and q each independently represent a positive integer.)

[0158]

[0159] (In formula (7), o, p, and q each independently represent a positive integer.)

[0160]

[0161] (In formula (8), o, p, q, and r each independently represent a positive integer.)

[0162] From the viewpoint of obtaining sufficient biodegradability, the content of the biodegradable segment (X) constituting the copolyester resin is preferably 5% by mass or more, and more preferably 10% by mass or more, relative to the copolyester resin (100% by mass). On the other hand, from the viewpoint of obtaining sufficient thermoformability, the content is preferably 50% by mass, and more preferably 45% by mass or less. These upper and lower limits may be used in any combination. The content is preferably 5% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 45% by mass or less.

[0163] From the viewpoint of obtaining sufficient thermoformability, the content of the non-biodegradable segment (Y) constituting the copolyester resin is preferably 50% by mass or more, and more preferably 55% by mass or more, relative to the copolyester resin (100% by mass). On the other hand, from the viewpoint of obtaining sufficient biodegradability, the content is preferably 95% by mass or less, and more preferably 90% by mass or less. These upper and lower limits may be used in any combination. The content is preferably 50% by mass or more and 95% by mass or less, and more preferably 55% by mass or more and 90% by mass or less.

[0164] From the viewpoint of obtaining sufficient biodegradability, the molar ratio (X / Y) of the biodegradable segment (X) to the non-biodegradable segment (Y) is 1 / 99 or more, preferably 5 / 95 or more, more preferably more than 5 / 95, further preferably more than 10 / 90, and particularly preferably more than 15 / 85. On the other hand, from the viewpoint of obtaining sufficient thermoformability, the molar ratio (X / Y) is less than 95 / 5, preferably less than 80 / 20, more preferably less than 70 / 30, and particularly preferably less than 50 / 50. These upper and lower limits can be used in any combination. The molar ratio (X / Y) is more than 1 / 99 and less than 95 / 5, preferably more than 5 / 95 and less than 95 / 5, more preferably more than 5 / 95 and less than 95 / 5, further preferably more than 10 / 90 and less than 80 / 20, further preferably more than 15 / 85 and less than 70 / 30, and particularly preferably more than 15 / 85 and less than 50 / 50.

[0165] From the viewpoint of obtaining sufficient biodegradability, the average chain length of the biodegradable segment (X) is greater than 1.2, preferably greater than 4.0, more preferably greater than 4.2, further preferably greater than 5.0, and particularly preferably greater than 5.5. On the other hand, from the viewpoint of obtaining sufficient thermoformability, the average chain length is preferably less than 30, more preferably less than 20, and further preferably less than 15. These upper and lower limits may be used in any combination. The average chain length is greater than 1.2 and less than 30, preferably greater than 4.0 and less than 30, more preferably greater than 4.2 and less than 20, further preferably greater than 5.0 and less than 20, and particularly preferably greater than 5.5 and less than 15.

[0166] From the viewpoint of obtaining sufficient thermoformability, the average chain length of the polymer segment (Y) is preferably 4.0 or more, more preferably 4.2 or more, and further preferably 5.0 or more. On the other hand, from the viewpoint of obtaining sufficient biodegradability, the average chain length is preferably 40.0 or less, more preferably 35 or less, and further preferably 30.0 or less. These upper and lower limits may be used in any combination. The average chain length is preferably 4.0 or more and 40.0 or less, more preferably 4.2 or more and 35 or less, and further preferably 5.0 or more and 30.0 or less.

[0167] From the viewpoint of processability and handling, the number average molecular weight (Mn) of the copolyester resin measured by gel permeation chromatography (GPC) in terms of polystyrene conversion is preferably 5,000 or more, more preferably 7,000 or more, further preferably 8,000 or more, and particularly preferably 10,000 or more. On the other hand, from the viewpoint of obtaining sufficient biodegradability, the number average molecular weight (Mn) is preferably 150,000 or less, more preferably 100,000 or less, further preferably 70,000 or less, and particularly preferably 50,000 or less. These upper and lower limits may be used in any combination. The number average molecular weight (Mn) is preferably 5,000 to 150,000, preferably 5,000 to 100,000, more preferably 7,000 to 100,000, more preferably 7,000 to 70,000, further preferably 10,000 to 70,000, further preferably 8,000 to 50,000.

[0168] From the viewpoint of processability and handling, the weight average molecular weight (Mw) of the copolyester resin measured by gel permeation chromatography (GPC) in terms of polystyrene conversion is preferably 7,000 or more, more preferably 10,000 or more, further preferably 15,000 or more, and particularly preferably 20,000 or more. On the other hand, from the viewpoint of obtaining sufficient biodegradability, the weight average molecular weight (Mw) is preferably 200,000 or less, more preferably 150,000 or less, and further preferably 100,000 or less. These upper and lower limits may be used in any combination. The weight average molecular weight (Mw) is preferably 7,000 to 200,000, preferably 10,000 to 200,000, more preferably 10,000 to 150,000, more preferably 15,000 to 150,000, further preferably 15,000 to 100,000, further preferably 20,000 to 100,000.

[0169] From the viewpoint of obtaining a resin having low dispersity and exhibiting desired properties, in the copolyester resin, the molecular weight distribution (Mw / Mn) obtained by dividing the value of the polystyrene-equivalent weight average molecular weight (Mw) measured by GPC by the value of the number average molecular weight (Mn) is preferably 4.5 or less, more preferably 4.0 or less, further preferably 3.7 or less, and particularly preferably 3.5 or less.

[0170] From the viewpoint of biodegradability, the randomness of the copolyester resin is preferably 0.07 or more, and more preferably 0.09 or more. On the other hand, from the viewpoint of thermoformability, the randomness of the copolyester resin is preferably 1.0 or less, and more preferably 0.9 or less. These upper and lower limits may be used in any combination. The randomness of the copolyester resin is preferably 0.07 or more and 1.0 or less, and more preferably 0.09 or more and 0.9 or less.

[0171] The melting point (Tm) of the copolyester resin is preferably 40° C. or higher, more preferably 65° C. or higher, more preferably 70° C. or higher, further preferably 95° C. or higher, further more preferably 100° C. or higher, and particularly preferably 102° C. or higher. On the other hand, the upper limit of the thermal decomposition temperature of the copolyester resin is not particularly limited, but is usually 250° C. or lower. When the melting point is within the above range, the hot workability during molding is excellent.

[0172] The biodegradation rate of the copolyester resin in a seawater environment is 15% or more because the copolyester resin needs to show "biodegradability" as referred to in the present invention. The seawater degradation rate is more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more.

[0173] Inoculum source: Seawater extracted from the coast of Akane Bay (near Akanehama, Narashino City, Chiba Prefecture) was used as the inoculum source.

[0174] Biodegradation Degree Measurement Method: Soda lime (carbon dioxide absorbent) and a pressure sensor (manufactured by WTW, OxiTop-IDS (registered trademark)) were placed in a test bottle, and BOD (biological oxygen demand) was measured under the following conditions to calculate the biodegradability.

[0175] Cultivation temperature: 27°C, dark

[0176] Cultivation time: 28 days

[0177] Calculation of biodegradability:

[0178] The biodegradability of the sample was calculated based on the following formula.

[0179] Biodegradability (%) = (BOD0-BODB) / ThOD×100

[0180] BOD0: Biochemical oxygen demand of the sample (measured value: mg)

[0181] BODB: Average biochemical oxygen demand of blank test (measured value: mg)

[0182] ThOD: Theoretical oxygen demand required for complete oxidation of the sample (calculated value: mg)

[0183] The biodegradability of the copolyester resin in a fresh water environment is preferably 15% or more, more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more.

[0184] In this specification, the biodegradability of the copolyester resin in freshwater environment is calculated by the same method as the above-mentioned seawater degradability except that river water extracted from the Inagawa River (near Taoyuan, Ikeda City, Hyogo Prefecture) is used as an inoculum source.

[0185] The biodegradability of the copolyester resin in a soil environment is preferably 15% or more, more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more.

[0186] In this specification, the biodegradability of the copolyester resin in soil environment is calculated by the same method as the above-mentioned seawater degradability except that soil extracted from Oshinozuka Citizen Farm (near Oshinozuka, Sakura City, Chiba Prefecture) is used as an inoculum source.

[0187] The compost degradation rate of the copolyester resin under composting conditions is preferably 15% or more, more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more.

[0188] In this specification, the compost degradation rate of the copolyester resin under composting conditions is a value determined by a method in accordance with JIS K6953-1:2011.

[0189] Cultivation temperature: 58°C

[0190] Cultivation time: 28 days

[0191] <Copolyester resin having triad units of unit (A) and unit (B)>

[0192] The copolyester resin of the present invention preferably contains two types of triad units (unit (A) and unit (B)) that exhibit biodegradability.

[0193] Among the two types of triad units exhibiting biodegradability contained in the copolyester resin of the present invention, one unit (unit (A)) is a unit derived from a structure represented by "first diol / dibasic acid / first diol" in which a first diol and a dibasic acid are bonded. In addition, the other unit (unit (B)) is a unit derived from a structure represented by "second diol / dibasic acid / second diol" in which a second diol of a different type from the first diol and a dibasic acid are bonded.

[0194] As a preferred combination of two types of triad units (unit (A) and unit (B)) exhibiting biodegradability contained in the copolyester resin of the present invention, for example, any one of the following (i) to (iii) can be mentioned.

[0195] (i)

[0196] Unit (A) is a triad unit derived from "a structure in which 2-methyl-1,3-propanediol, adipic acid and 2-methyl-1,3-propanediol are bonded together", and unit (B) is a triad unit derived from "a structure in which 1,4-butanediol, adipic acid and 1,4-butanediol are bonded together",

[0197] (ii)

[0198] Unit (A) is a triad unit derived from "a structure in which 2-methyl-1,3-propanediol, sebacic acid and 2-methyl-1,3-propanediol are bonded together", and unit (B) is a triad unit derived from "a structure in which 1,4-butanediol, sebacic acid and 1,4-butanediol are bonded together", or

[0199] (iii)

[0200] Unit (A) is a triad unit derived from "a structure in which 3-methyl-1,5-pentanediol, adipic acid and 3-methyl-1,5-pentanediol are bonded together", and unit (B) is a triad unit derived from "a structure in which 1,4-butanediol, adipic acid and 1,4-butanediol are bonded together", and any of the above is preferred.

[0201] (Method for producing copolyester resin)

[0202] The copolyester resin of the present invention can be produced by a common method for producing a copolyester resin, but preferably a polyester exchange reaction is used from the viewpoint of easily obtaining a copolyester resin having a desired average chain length.

[0203] The method for producing a copolyester resin of the present invention preferably comprises, in the method for producing a copolyester resin comprising a combination of a biodegradable segment (X) derived from a polymer (x) containing a structural unit having biodegradability and a non-biodegradable segment (Y) derived from a polymer (y) containing a structural unit having non-biodegradability, a step of obtaining a block copolymer comprising a biodegradable segment (X) and a non-biodegradable segment (Y) by subjecting the polymer (x) and the polymer (y) to an ester exchange reaction.

[0204] As a preferred embodiment of the method for producing the copolyester resin of the present invention, for example, there can be cited a method comprising the following steps:

[0205] A step of synthesizing a polymer (x) containing a biodegradable structural unit by polycondensing a hydroxyalkanoic acid or a dibasic acid with a diol;

[0206] A step of synthesizing a polymer (y) containing a structural unit having non-biodegradability; and

[0207] A step of subjecting a polymer (x) and a polymer (y) to transesterification reaction to obtain a block copolymer comprising a biodegradable segment (X) and a non-biodegradable segment (Y).

[0208] <Steps for synthesizing polymer (x) and polymer (y)>

[0209] The synthesis method of polymer (x) and polymer (y) is not particularly limited, and a common synthesis method of polyester resin can be used. For example, the following describes a case where polymer (y) is a polyester resin containing a structural unit derived from a structure formed by bonding a dibasic acid other than the dibasic acid represented by the above formula (1) and a diol.

[0210] As the dibasic acid and diol used as the raw materials in the synthesis of the polymer (x) or the polymer (y), the compounds described in the section of the polymer (x) containing a biodegradable structural unit or the polymer (y) containing a non-biodegradable structural unit can be used.

[0211] The raw materials used in the synthesis of polymer (x) or polymer (y) may optionally contain other raw materials in addition to the dibasic acid and diol. The other raw materials are not particularly limited, and examples thereof include trivalent or higher polyols and trivalent or higher polycarboxylic acids.

[0212] The mixing ratio of the dibasic acid and the diol is not particularly limited, but is preferably 90:10 to 50:50, more preferably 80:20 to 50:50, in terms of mass ratio (dibasic acid:diol).

[0213] The reaction can be carried out without a catalyst or in the presence of a catalyst. As the catalyst used in the reaction, for example, an acid catalyst can be cited. As the acid catalyst, for example, tin catalysts such as monobutyl tin oxide and dibutyl tin oxide, titanium catalysts such as tetraisopropyl titanate (titanium tetraisopropoxide), acetylacetonate titanium, zirconium oxide catalysts such as tetrabutyl zirconate, etc. can be cited. From the perspective of improving the activity of transesterification and esterification reactions, titanium catalysts are preferably used. As titanium catalysts, titanium tetramethoxide, tetraethyl titanate, tetraisopropyl titanate, tetra-n-propyl titanate, tetra-n-butyl titanate, tetra(2-ethylhexyloxy) titanium, tetra(stearyloxy) titanium (tetra stearyloxytitanium), etc., are listed. From the perspective of stability in handling and activity as a catalyst, tetraisopropyl titanate is preferred.

[0214] The amount of the catalyst used is usually in the range of 0.001 to 5.0% by mass relative to the total mass of the dibasic acid and the diol.

[0215] Water and lower alcohols are produced as by-products in the reaction for synthesizing the polymer (x) or the polymer (y). By removing these from the reaction system in the reaction step, the condensation reaction can proceed more easily.

[0216] The reaction temperature is not particularly limited and is usually 50 to 300° C. The reaction atmosphere may be air or an inert gas atmosphere such as nitrogen or argon. The reaction time is usually 1 to 48 hours, and the reaction is preferably carried out until the dibasic acid or diol as a raw material does not remain in the reaction system. The reaction can be carried out, for example, by tracking the reduction of the dibasic acid using an acid value measurement.

[0217] <Production process of copolyester resin by transesterification reaction>

[0218] The method for synthesizing a polymer by transesterification reaction is not particularly limited, and a common method for synthesizing a polymer by transesterification reaction can be used.

[0219] As the catalyst used in the transesterification reaction, a titanium catalyst is preferably used. Examples of the titanium catalyst include: titanium tetramethoxide, tetraethyl titanate, tetraisopropyl titanate, tetra-n-propyl titanate, tetra-n-butyl titanate, tetra(2-ethylhexyl) titanium, tetra(stearyl) titanium, etc., and tetraisopropyl titanate is preferred from the viewpoint of stability in handling and activity as a catalyst.

[0220] The amount of the catalyst used is usually in the range of 0.001 to 5.0% by mass based on the total mass of the polymer (x) and the polymer (y).

[0221] The reaction temperature is not particularly limited, but is usually 50 to 300° C. The reaction atmosphere may be air or an inert gas atmosphere such as nitrogen or argon.

[0222] The reaction time is usually 1 to 48 hours.

[0223] (Polyurethane)

[0224] As one embodiment of the copolyester resin obtained as described above, polyurethane can be mentioned.

[0225] The polyurethane is obtained by reacting the copolyester of the present invention with a polyisocyanate. If necessary, a polyol other than the copolyester, a chain extender, a chain terminator, and a crosslinking agent may be used in combination.

[0226] Specifically, polyurethane is obtained by reacting polyol with polyisocyanate, and as polyol, at least copolyester of the present invention can be used. Therefore, polyurethane is a reaction product obtained by reacting polyol with polyisocyanate, and polyurethane has structural units derived from polyol and structural units derived from polyisocyanate, and at least has structural units derived from copolyester of the present invention.

[0227] The copolyesters of the present invention are preferably polyester polyols.

[0228] Examples of the polyester polyol include condensed polyester polyols, which are, for example, reaction products of low molecular weight polyols (low molecular weight polyols such as ethylene glycol (EG), diethylene glycol, propylene glycol (PG), dipropylene glycol, (1,3- or 1,4-)butanediol, pentanediol, neopentyl glycol, hexanediol, cyclohexanedimethanol, glycerol, 1,1,1-trimethylolpropane (TMP), 1,2,5-hexanetriol, pentaerythritol, and sugars such as sorbitol) and polycarboxylic acids (glutaric acid, adipic acid, azelaic acid, fumaric acid, maleic acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, terephthalic acid, isophthalic acid, dimer acid, pyromellitic acid, oligomeric acids, and the like).

[0229] As the chain extender, for example, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, hexylene glycol, sucrose, methylene glycol, The chain extenders include aliphatic polyol compounds such as 1,2-dihydroxy-2-nitropropene, 1,4 ...

[0230] The content of the copolyester of the present invention in 100% by mass of the polyol is preferably 10 to 100% by mass, more preferably 50 to 100% by mass.

[0231] As the polyisocyanate, for example, 1,3- and 1,4-phenylene diisocyanate, 1-methyl-2,4-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-2,5-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-3,5-phenylene diisocyanate, 1-ethyl-2,4-phenylene diisocyanate, 1-isopropyl-2,4-phenylene diisocyanate, 1,3-dimethyl-2,4-phenylene diisocyanate, 1,3-dimethyl 1,4-dimethyl-2,5-phenylene diisocyanate, diethylphenylene diisocyanate, diisopropylphenylene diisocyanate, 1-methyl-3,5-diethylphenylene diisocyanate, 3-methyl-1,5-diethylbenzene-2,4-diisocyanate, 1,3,5-triethylbenzene-2,4-diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, 1-methyl-naphthalene-1,5-diisocyanate, naphthalene-2,6-diisocyanate, naphthalene-2,7-diisocyanate, 1 , 1-dinaphthyl-2,2'-diisocyanate, biphenyl-2,4'-diisocyanate, biphenyl-4,4'-diisocyanate, 3,3'-dimethylbiphenyl-4,4'-diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, diphenylmethane-2,4-diisocyanate, toluene diisocyanate and other aromatic polyisocyanates; tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate and other aliphatic polyisocyanates Acid ester; 1,3-cyclopentylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, lysine diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate, 2,2'-dicyclohexylmethane diisocyanate, 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate and other alicyclic polyisocyanates. These can be used alone or in combination of two or more. Among them, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-diphenylmethane diisocyanate, and toluene diisocyanate are more preferred.

[0232] For the purpose of controlling the molecular weight of the obtained polyurethane, a chain terminator having one active hydrogen may be used as required. Examples of the chain terminator include aliphatic monohydroxy compounds such as methanol, ethanol, propanol, butanol and hexanol having a hydroxyl group, and aliphatic monoamines such as morpholine, diethylamine, dibutylamine, monoethanolamine and diethanolamine having an amino group. These may be used alone or in combination of two or more.

[0233] For the purpose of improving the heat resistance and strength of the obtained polyurethane, a crosslinking agent having three or more active hydrogen groups or isocyanate groups may be used as necessary.

[0234] Polyurethane can be obtained by a known method for producing polyurethane. Specifically, for example, a method for producing by adding a polyol, a polyisocyanate and the aforementioned chain extender and reacting them can be cited. These reactions are preferably carried out at a temperature of 50 to 100° C. for 3 to 10 hours. In addition, the reaction can be carried out in an organic solvent.

[0235] As the organic solvent, for example, ketone solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, methyl ethyl ketone, methyl n-propyl ketone, acetone, and methyl isobutyl ketone; ester solvents such as methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, isopropyl acetate, isobutyl acetate, isobutyl acetate, and sec-butyl acetate; etc. These organic solvents may be used alone or in combination of two or more.

[0236] The content of the structural unit derived from the copolyester of the present invention in 100% by mass of the polyurethane is preferably 10 to 98% by mass, more preferably 20 to 98% by mass.

[0237] This tends to result in more favorable effects.

[0238] In this specification, the content of each structural unit in the polyurethane is measured by NMR.

[0239] The lower limit of the number average molecular weight (Mn) of the polyurethane may be 5,000 or more, 6,000 or more, 7,000 or more, 8,000 or more, or 10,000 or more, and the upper limit may be 1,000,000 or less, 500,000 or less, 100,000 or less, 500,000 or less, or 15,000 or less. These upper and lower limits may be used in any combination.

[0240] The number average molecular weight (Mn) of the polyurethane may be 5,000 to 1,000,000, 6,000 to 500,000, 7,000 to 100,000, 8,000 to 500,000, or 10,000 to 15,000.

[0241] If it is within the above range, there is a tendency that the effect can be obtained more preferably. In addition, in this specification, the number average molecular weight (Mn) of polyurethane is a value measured by GPC.

[0242] (Resin composition)

[0243] Examples of the resin composition of the present embodiment include a thermoplastic resin composition or a thermosetting resin composition containing the above-described copolyester and polyurethane of the present embodiment.

[0244] <Thermoplastic resin composition>

[0245] When the resin composition of the present embodiment is a thermoplastic resin composition, for example, other resins, a crystal nucleating agent, a heat stabilizer, an anti-hydrolysis agent, other additives, etc. may be further included as necessary.

[0246] <<Crystallization nucleating agent>>

[0247] The crystal nucleating agent used in the thermoplastic resin composition of the present embodiment may be any crystal nucleating agent as long as it is a crystal nucleating agent used in thermoplastic resins derived from biomass resources such as polylactic acid and polybutylene succinate. For example, it is preferred to use a talc-based nucleating agent, a nucleating agent containing a metal salt-based material having a phenyl group, a nucleating agent containing a benzoyl compound-based nucleating agent, etc. Other known crystal nucleating agents, such as lactate, benzoate, silica, phosphate salt-based, etc., may also be used.

[0248] <<Heat stabilizer and anti-hydrolysis agent>>

[0249] The thermoplastic resin composition of the present embodiment preferably includes a phenolic antioxidant and a phosphite antioxidant as a heat stabilizer for the resin composition, and includes a carbodiimide compound-based anti-hydrolysis agent such as a polycarbodiimide resin (trade name: CARBODILITE, manufactured by Nisshinbo Chemical Co., Ltd.) as an anti-hydrolysis agent. The added heat stabilizer and anti-hydrolysis agent can be one selected from the above three additives, but the above two heat stabilizers and anti-hydrolysis agents have different functions, and preferably all additives are added. The amount of heat stabilizer and anti-hydrolysis agent added varies depending on the type, and is generally preferably about 0.1 to 5 parts by mass relative to 100 parts by mass of the thermoplastic resin composition.

[0250] <<Other additives>>

[0251] In the thermoplastic resin composition of the present embodiment, it is also preferred to add an organosilicon flame retardant, an organometallic salt flame retardant, an organophosphorus flame retardant, a metal oxide flame retardant, a metal hydroxide flame retardant, etc. This can improve the flame retardancy to suppress the spread of fire, and improve the fluidity of the biodegradable resin composition, thereby ensuring better moldability.

[0252] Fillers may be added to the thermoplastic resin composition of the present embodiment. Examples of fillers include talc, mica, montmorillonite, and kaolin. By making these fillers into crystal nuclei, the crystallization of the copolyester is promoted, and the impact strength and heat resistance of the molded body are improved. In addition, the rigidity of the molded body can also be increased.

[0253] In the thermoplastic resin composition of the present embodiment, it is also possible to appropriately mix: antioxidants, anti-blocking agents, colorants, flame retardants, mold release agents, anti-fogging agents, surface wettability improvers, incineration aids, lubricants, dispersing aids, various surfactants, plasticizers, extenders, weatherability improvers, ultraviolet absorbers, processing aids, antistatic agents, colorants, lubricants, various additives such as release agents. As plasticizers, known plasticizers commonly used as plasticizers for polymers can be used without particular restrictions, for example, polyester plasticizers, glycerol plasticizers, polycarboxylic acid ester plasticizers, polyalkylene glycol plasticizers and epoxy plasticizers can be listed. Extenders are not particularly limited as long as they play the role of extenders for copolymers A and B. As extenders, inorganic fillers, glycidyl compounds, polymer compounds formed by grafting or copolymerizing acid anhydrides, and organometallic compounds can be listed, and one or more of these can be used. By kneading these, heat resistance, flexural strength, impact strength, flame retardancy, etc. can also be improved, and thus the application to molded products such as housings for electronic devices represented by notebook computers, mobile phones, etc. is further promoted.

[0254] In addition, various fillers known in the past may be mixed as fillers. As functional additives, chemical fertilizers, soil conditioners, plant active agents, etc. may also be added. The fillers are roughly divided into inorganic fillers and organic fillers. One of these or a mixture of two or more may also be used.

[0255] Examples of the inorganic filler include anhydrous silica, mica, talc, titanium oxide, calcium carbonate, diatomaceous earth, allophane, bentonite, potassium titanate, zeolite, sepiolite, montmorillonite, kaolin, kaolinite, glass, limestone, carbon, wollastonite, calcined perlite, silicates such as calcium silicate and sodium silicate, hydroxides such as aluminum oxide, magnesium carbonate and calcium hydroxide, iron carbonate, zinc oxide, iron oxide, aluminum phosphate, barium sulfate and the like. The content of the inorganic filler is usually 1 to 80% by weight, preferably 3 to 70% by weight, and more preferably 5 to 60% by weight in the total composition.

[0256] Examples of organic fillers include raw starch, processed starch, pulp, chitin / chitosan, coconut shell powder, wood powder, bamboo powder, bark powder, kenaf, straw powder, etc. One or a mixture of two or more of these may also be used. The amount of organic filler added is usually 0.01 to 70% by weight of the total composition.

[0257] The preparation of the composition can apply all the previously known mixing / kneading techniques. As a mixer, a mixer such as a horizontal cylindrical type, a V-shaped, a double cone type mixer, a ribbon mixer, a high-speed mixer, and various continuous mixers can be used. In addition, as a kneading machine, an intermittent kneading machine such as a roller or a banbury mixer, a one-stage type, a two-stage type continuous kneading machine, a twin screw extruder, a single screw extruder, etc. can be used. As a method for kneading, various additives, fillers, thermoplastic resins, and compounding methods can be listed when heated and melted. In addition, in order to evenly disperse the aforementioned various additives, mixing oils can also be used.

[0258] <Thermosetting resin composition>

[0259] When the resin composition of this embodiment is a thermosetting resin composition, for example, it contains other resins, the copolyester of this embodiment having reactive groups such as hydroxyl groups and carboxyl groups as a thermosetting resin main agent, and also contains curing agents such as isocyanate curing agents and polyamine curing agents that can thermally react with the aforementioned reactive groups.

[0260] Examples of the curing agent of the present embodiment include: polyisocyanates having an aromatic structure in their molecular structures, such as toluene diisocyanate, diphenylmethane diisocyanate, polymerized diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and xylylene diisocyanate; compounds obtained by modifying a part of the isocyanate groups of these polyisocyanates with carbodiimide; allophanate compounds derived from these polyisocyanates; polyisocyanates having an alicyclic structure in their molecular structures, such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl diisocyanate), and 1,3-bis(isocyanatomethyl)cyclohexane; 1,6-hexamethylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and the like. Straight-chain aliphatic polyisocyanates such as cyanate, and allophanate compounds thereof; isocyanurate forms of these polyisocyanates; allophanate forms derived from these polyisocyanates; biuret forms derived from these polyisocyanates; trimethylolpropane-modified adducts; polyisocyanates such as polyisocyanates which are reaction products of the aforementioned various polyisocyanates and polyol components, polyfunctional isocyanates, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexyleneheptamine, heptaethyleneoctamine, octaethylenenonamine, nonaethylenedecaamine, piperazine or N-aminoalkylpiperazine having an alkyl chain having 2 to 6 carbon atoms, and amine compounds such as 3-aminomethyl-3,5,5-trimethylcyclohexylamine (isophoronediamine or IPDA).

[0261] <Cured product of resin composition>

[0262] The cured product of the resin composition of the present embodiment is a cured product of the resin composition which is the aforementioned thermoplastic resin composition or a cured product of the resin composition which is the aforementioned thermosetting resin composition.

[0263] The polymers in this specification can be used for various purposes. Specifically, they can be used for a wide range of purposes such as artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, coatings, laminating adhesives, elastic fibers, urethane raw materials, automobile parts, sporting goods, vibration-proof materials, vibration-damping materials, fiber treatment agents, adhesives, etc.

[0264] Copolyesters can be used in a variety of applications, including artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, coatings, laminating adhesives, elastic fibers, urethane raw materials, automobile parts, sporting goods, and the like.

[0265] Polyurethane can be used in a variety of applications. Specifically, it can be used in a wide range of applications such as artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, coatings, laminating adhesives, vibration-proof materials, vibration-damping materials, automobile parts, sporting goods, fiber treatment agents, adhesives, etc.

[0266] (Coating agent)

[0267] The coating agent contains the copolyester resin of the present invention and, if necessary, other components such as other resins, water, and an organic solvent.

[0268] The coating agent can be applied to various substrates. An example of the use of the coating agent is described below.

[0269] The coating agent can be used as a surface coating of a substrate of a food packaging container, for example. As the substrate, for example, plastic films such as styrene resin films, polyolefin resin films, polyester resin films, nylon resin films, or laminates thereof can be cited. As the substrate, for example, paper, metallized films, aluminum foil, etc. can be cited. The coating agent can be appropriately used for biodegradable substrates. As the biodegradable substrate, for example, paper, polyester films, polyolefin films, starch films, etc. can be cited.

[0270] The coating agent can be used as ink, an adhesive, or the like.

[0271] (ink)

[0272] The ink contains the copolyester resin of the present invention and a colorant, and may contain other components such as a pigment dispersant, water, and an organic solvent as necessary.

[0273] The ink is, for example, printing ink.

[0274] The ink may be, for example, a water-based ink or an ink not containing water (solvent-based ink).

[0275] (Adhesive)

[0276] The adhesive contains the copolyester resin of the present invention and, if necessary, other components such as other resins, a curing agent, and an organic solvent.

[0277] The adhesive can also be used as an adhesive composition for lamination to be used when laminating on the above-mentioned various substrates to produce a composite film mainly used as a packaging material for food, medicines, detergents, etc.

[0278] Such adhesives may be, for example, two-component curing adhesives containing the copolyester resin of the present invention, polymer polyols, and polyisocyanates, or one-component adhesives containing acrylic resins, urethane resins, and ethylene-vinyl acetate copolymers. These adhesives may be solvent-based, solvent-free, water-based, or alcohol-based adhesives as required.

[0279] (piece)

[0280] The sheet is formed by using a resin composition containing the copolyester resin of the present invention. The resin composition may contain other resins and various additives in addition to the copolyester resin of the present invention. Examples of the various additives include plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, lubricants, antiblocking agents, and thermal stabilizers.

[0281] Examples of the sheet include a non-stretched sheet, a biaxially stretched sheet, and a foamed sheet.

[0282] The application of the sheet is not particularly limited, and for example, it can be widely used in food packaging containers, building materials, home appliances, sundries, and the like.

[0283] (film)

[0284] The film is formed by using a resin composition containing the copolyester resin of the present invention. The resin composition may contain other resins and various additives in addition to the copolyester resin of the present invention. Examples of the various additives include plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, lubricants, antiblocking agents, and thermal stabilizers.

[0285] Examples of the film include non-stretched films, biaxially stretched films, and uniaxially stretched films, which can be produced by, for example, melting pellets of a film raw material with an extruder and then forming a film with a T-die or a blow molding method. In the T-die method, the film is stretched longitudinally using a roller speed difference and stretched transversely using a tenter to obtain a biaxially stretched film.

[0286] (Laminated body)

[0287] The laminate has at least one selected from the sheet and film of the present embodiment, and further has other structures such as a printed layer and a resin film as necessary.

[0288] The laminate is obtained by laminating a film or sheet to one or both sides of at least one of the sheets and films selected from the present embodiment in order to improve mechanical strength, chemical resistance, etc. Specifically, a polystyrene blown film is thermally laminated on at least one side of the front side and the back side of the sheet or film, or an olefin film (CPP) is laminated using an adhesive.

[0289] The adhesive to be used is not particularly limited, and may be, for example, the adhesive of the present embodiment or a known adhesive.

[0290] (Molding body)

[0291] The molded product can be obtained by molding at least one selected from the sheet, film, and laminate of the present embodiment.

[0292] The molded body can be obtained by, for example, thermoforming the sheet, film, and laminate of the present embodiment. Examples of thermoforming methods include: hot plate contact heating molding, vacuum molding, vacuum pressure molding, plug-assisted molding, etc. In particular, indirect heating molding using an infrared heater as a heat source can be preferably used.

[0293] Example

[0294] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0295] <Evaluation of chemical structure>

[0296] The chemical structures of the resins in the examples and comparative examples were determined using nuclear magnetic resonance ( 13 C-NMR) and was identified under the following conditions.

[0297] Measuring device: JEOL RESONANCE "JNM-ECM400S"

[0298] Magnetic field strength: 100MHz

[0299] Scan times: 1000 times

[0300] Solvent: deuterated chloroform

[0301] Paramagnetic relaxation reagent: Chromium(III) acetoacetate

[0302] Sample concentration: 200mg / 1.0mL

[0303] <Evaluation of average chain length>

[0304] <<Calculation of Peak Integration Value>>

[0305] The obtained 13 The C-NMR spectrum was subjected to waveform separation processing, and the triad peak integral value was calculated.

[0306] <<Calculation of average chain length of quaternary polyester>>

[0307] The average chain length was calculated based on the following formula.

[0308] L x-y =(I x-y-x ×2) / (I x-w-x +I z-y-x +I z-y-x +I x-y-z+I y-x-w )+1

[0309] L: average chain length

[0310] I: Triad peak integral value

[0311] x: Structural unit derived from 2-methyl-1,3-propanediol

[0312] y: structural unit derived from adipic acid

[0313] z: Structural unit derived from 1,4-butanediol

[0314] w: Structural unit derived from succinic acid

[0315] [Calculation of average chain length of copolyester containing hydroxyalkanoic acid]

[0316] The average chain length was calculated based on the following formula.

[0317] L h-h =1+2×(I s-h-h +I h-h-h ) / (I s-h-b +I h-h-b +I b-s-h +I h-s-h )

[0318] L: average chain length

[0319] I: Triad peak integral value

[0320] h: structural unit derived from 6-hydroxyhexanoic acid

[0321] s: Structural unit derived from succinic acid

[0322] b: Structural unit derived from 1,4-butanediol

[0323] <Evaluation of Molecular Weight>

[0324] In Examples and Comparative Examples, the molecular weight of the resin is a value measured under the following conditions using gel permeation chromatography (GPC).

[0325] Measurement device: System controller Waters 600Controller

[0326] Liquid delivery pump Waters Model Code 60F

[0327] RI (differential refractometer) detector Waters 2414

[0328] Waters 717plus Autosampler

[0329] Data processing: Waters Empower3

[0330] Measurement conditions

[0331] Measurement conditions: column temperature 40°C

[0332] Eluent: Chloroform (CHCl3)

[0333] Flow rate 1.0ml / min

[0334] Standard: Polystyrene

[0335] Column: Shodex GPC LF-G 1 piece

[0336] Shodex GPC LF-804 4pcs

[0337] Sample: A solution obtained by filtering a chloroform solution having a concentration of 0.4% by mass in terms of resin solid content with a microfilter (100 μl)

[0338] <Evaluation of acid value>

[0339] In Examples and Comparative Examples, the acid value of the resin was calculated by the following procedure.

[0340] About 1 g of the sample was weighed in a stoppered Erlenmeyer flask, 20 mL of acetone was added to dissolve it, phenolphthalein test solution was added as an indicator, and the mixture was kept for 30 seconds. Then, 0.1 N alcoholic potassium hydroxide solution was used to titrate the solution until it turned light red, and the acid value was calculated using the following formula.

[0341] Acid value (mgKOH / g) = (5.611×a×F) / S

[0342] S: Extraction amount of sample (g)

[0343] a: Consumption of 0.1N alcoholic potassium hydroxide solution (mL)

[0344] F: Factor of 0.1N alcoholic potassium hydroxide solution

[0345] <Melting point measurement>

[0346] Measuring device: DSC822 manufactured by Mettler

[0347] Measurement conditions: Under nitrogen flow, temperature rise and fall rate 5℃ / min, measurement temperature range -60℃~180℃

[0348] <Evaluation of biodegradability>

[0349] In Examples and Comparative Examples, the biodegradability was evaluated based on the biodegradability calculated by the following procedure.

[0350] <<Evaluation of seawater degradability>>

[0351] Inoculum source: Seawater extracted from the coast of Akane Bay (near Akanehama, Narashino City, Chiba Prefecture) was used as the inoculum source.

[0352] Biodegradation Degree Measurement Method: Soda lime (carbon dioxide absorbent) and a pressure sensor (manufactured by WTW, OxiTop-IDS (registered trademark)) were placed in a test bottle, and BOD (biological oxygen demand) was measured under the following conditions to calculate the biodegradation degree.

[0353] Cultivation temperature: 27°C, dark

[0354] Cultivation time: 28 days

[0355] Calculation of biodegradability:

[0356] The biodegradability of the resin samples of Examples or Comparative Examples was calculated based on the following formula.

[0357] Biodegradability (%) = (BOD0-BODB) / ThOD×100

[0358] BOD0: Biochemical oxygen demand of the sample (measured value: mg)

[0359] BODB: Average biochemical oxygen demand of blank test (measured value: mg)

[0360] ThOD: Theoretical oxygen demand required for complete oxidation of the sample (calculated value: mg)

[0361] Evaluation criteria:

[0362] A (optimal): biodegradability is more than 50%

[0363] B (excellent): biodegradability is 40% or more and less than 50%

[0364] C (good): biodegradability is 24% or more and less than 40%

[0365] D (permissible): Biodegradability is 15% or more and less than 24% (practical lower limit)

[0366] E (Not applicable): Biodegradability is less than 15% (not suitable for practical use)

[0367] <<Evaluation of fresh water degradability>>

[0368] The degradability was evaluated by the same operation as the method described in the evaluation of seawater degradability, except that the inoculation source was river water extracted from the Inagawa River (near Taoyuan, Ikeda City, Hyogo Prefecture).

[0369] <<Evaluation of soil degradability>>

[0370] Degradability was evaluated by the same procedure as described in the evaluation of seawater degradability, except that the inoculum source was soil extracted from Oshinozuka Citizens' Farm (near Oshinozuka, Sakura City, Chiba Prefecture).

[0371] <<Evaluation of compostability>>

[0372] The composting degradation rate was measured by a method in accordance with JIS K6953-1:2011.

[0373] Cultivation temperature: 58°C

[0374] Cultivation time: 28 days

[0375] Evaluation criteria:

[0376] A (optimal): composting degradation rate is more than 50%

[0377] B (excellent): composting degradation rate is more than 40% and less than 50%

[0378] C (good): composting degradation rate is above 24% and less than 40%

[0379] D (acceptable): Composting degradation rate is 15% or more and less than 24% (practical lower limit)

[0380] E (Not applicable): Composting rate is less than 15% (not suitable for practical use)

[0381] (Synthesis example 1)

[0382] <Synthesis of poly(2-methyl-1,3-propanediol / adipic acid) (P(2MPD / AA))>

[0383] 396 parts by mass of 2-methyl-1,3-propanediol (2MPD), 604 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added to a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, and an esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 200° C. and the vapor temperature at 98° C. under a nitrogen flow. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less to obtain P(2MPD / AA). The structure of P(2MPD / AA) is shown in formula (9).

[0384]

[0385] (In formula (9), a represents a positive integer.)

[0386] The biodegradability evaluation results showed that the biodegradability in the seawater was 63%, the biodegradability in the fresh water was 65%, the biodegradability in the soil was 78%, and the compost degradation rate was 83%. The number average molecular weight Mn was 10071, and the weight average molecular weight Mw was 31524.

[0387] (Synthesis example 2)

[0388] <Synthesis of poly(1,4-butylene glycol / succinic acid) (P(BG / SA))>

[0389] P(BG / SA) was obtained in the same manner as in Synthesis Example 1 except that 441 parts by mass of 1,4-butanediol (BG), 559 parts by mass of succinic acid (SA), and 0.2 parts by mass of tetraisopropyl titanate (TIPT) were used as raw materials and the liquid temperature of the reaction liquid was set to 220°C. The structure of P(BG / SA) is shown in Formula (10).

[0390]

[0391] (In formula (10), b represents a positive integer.)

[0392] The evaluation results of biodegradability showed that the biodegradability in the seawater was 3%, the biodegradability in the fresh water was 3%, the biodegradability in the soil was 10%, and the compost degradation rate was 13%. The number average molecular weight Mn was 12254, and the weight average molecular weight Mw was 28416.

[0393] (Synthesis example 3)

[0394] <Synthesis of poly(2-methyl-1,3-propanediol / sebacic acid) (P(2MPD / SebA))>

[0395] P(2MPD / SebA) was obtained in the same manner as in Synthesis Example 1 except that 322 parts by mass of 2-methyl-1,3-propanediol (2MPD), 678 parts by mass of sebacic acid (SebA), and 0.2 parts by mass of tetraisopropyl titanate (TIPT) were used as raw materials. The structure of P(2MPD / SebA) is shown in Formula (11).

[0396]

[0397] (In formula (11), c represents a positive integer.)

[0398] The biodegradability evaluation results showed that the biodegradability in the seawater was 65%, the biodegradability in the fresh water was 65%, the biodegradability in the soil was 74%, and the compost degradation rate was 83%. The number average molecular weight Mn was 19587, and the weight average molecular weight Mw was 63356.

[0399] (Synthesis Example 4)

[0400] <Synthesis of poly(3-methyl-1,5-propanediol / adipic acid) (P(3MPD / AA))>

[0401] P(3MPD / AA) was obtained in the same manner as in Synthesis Example 1 except that 458 parts by mass of 3-methyl-1,5-propanediol (3MPD), 542 parts by mass of adipic acid (AA), and 0.2 parts by mass of tetraisopropyl titanate (TIPT) were used as raw materials. The structure of P(3MPD / AA) is shown in Formula (12).

[0402]

[0403] (In formula (12), d represents a positive integer.)

[0404] The biodegradability evaluation results showed that the biodegradability in the seawater was 63%, the biodegradability in the fresh water was 64%, the biodegradability in the soil was 78%, and the compost degradation rate was 85%. The number average molecular weight Mn was 13880, and the weight average molecular weight Mw was 42954.

[0405] (Synthesis Example 5)

[0406] <Synthesis of poly(1,4-butylene glycol / adipic acid / terephthalic acid) (P(BG / AA / tPA))>

[0407] P(BG / AA / tPA) was obtained in the same manner as in Synthesis Example 1 except that 398 parts by mass of 1,4-butanediol (BG), 292 parts by mass of adipic acid (AA), 332 parts by mass of terephthalic acid (tPA), and 0.2 parts by mass of tetraisopropyl titanate (TIPT) were used as raw materials and the liquid temperature of the reaction liquid was set to 220°C. The structure of P(BG / AA / tPA) is shown in Formula (13).

[0408]

[0409] (In formula (13), e and f each independently represent a positive integer.)

[0410] The evaluation results of biodegradability showed that the biodegradability in the seawater was 3%, the biodegradability in the fresh water was 3%, the biodegradability in the soil was 8%, and the compost degradation rate was 10%. The average molecular weight was measured as follows: the number average molecular weight Mn was 26445, and the weight average molecular weight Mw was 81430.

[0411] (Synthesis Example 6)

[0412] <Synthesis of poly(ethylene glycol / adipic acid) (P(EG / AA))>

[0413] Into a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, 306 parts by mass of ethylene glycol (EG), 694 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added, and an esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 190°C and the vapor temperature at 98°C under a nitrogen flow. The reaction was terminated when the acid value of the reaction liquid became less than 2 mgKOH / g to obtain P(EG / AA). The structure of P(EG / AA) is shown in formula (14).

[0414]

[0415] (In formula (14), a represents a positive integer.)

[0416] The evaluation results of biodegradability showed that the biodegradability in seawater was 50%, the biodegradability in fresh water was 52%, the biodegradability in soil was 55%, and the compost degradation rate was 65%. The number average molecular weight Mn was 5568, and the weight average molecular weight Mw was 14619.

[0417] (Synthesis Example 7)

[0418] <Synthesis of poly(diethylene glycol / adipic acid) (P(DEG / AA))>

[0419] Into a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, 431 parts by mass of diethylene glycol (DEG), 569 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added, and an esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C under a nitrogen flow. The reaction was terminated when the acid value of the reaction liquid became less than 2 mgKOH / g to obtain P(DEG / AA). The structure of P(DEG / AA) is shown in formula (15).

[0420]

[0421] (In formula (15), a represents a positive integer.)

[0422] The evaluation results of biodegradability showed that the biodegradability in the seawater was 63%, the biodegradability in the fresh water was 65%, the biodegradability in the soil was 70%, and the compost degradation rate was 78%. The number average molecular weight Mn was 14200, and the weight average molecular weight Mw was 102600.

[0423] (Synthesis Example 8)

[0424] <Synthesis of poly(1,2-propylene glycol / adipic acid) (P(1,2PG / AA))>

[0425] Into a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, 351 parts by mass of 1,2-propylene glycol (1,2PG), 649 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added, and an esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C under a nitrogen flow. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less to obtain P(1,2PG / AA). The structure of P(1,2PG / AA) is shown in formula (16).

[0426]

[0427] (In formula (16), a represents a positive integer.)

[0428] The biodegradability evaluation results showed that the biodegradability in the seawater was 71%, the biodegradability in the fresh water was 67%, the biodegradability in the soil was 75%, and the compost degradation rate was 81%. The number average molecular weight Mn was 6870, and the weight average molecular weight Mw was 14070.

[0429] (Synthesis Example 9)

[0430] <Synthesis of poly(1,3-butylene glycol / adipic acid) (P(1,3BG / AA))>

[0431] 391 parts by mass of 1,3-butanediol (1,3BG), 609 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added to a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator. Under a nitrogen flow, the esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 190° C. and the vapor temperature at 98° C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less to obtain P(1,3BG / AA). The structure of P(1,3BG / AA) is shown in Formula (17).

[0432]

[0433] (In formula (17), a represents a positive integer.)

[0434] The evaluation results of biodegradability showed that the biodegradability in the seawater was 60%, the biodegradability in the fresh water was 59%, the biodegradability in the soil was 63%, and the compost degradation rate was 78%. The number average molecular weight Mn was 14700, and the weight average molecular weight Mw was 92000.

[0435] (Synthesis Example 10)

[0436] <Synthesis of poly(1,3-propylene glycol / adipic acid) (P(1,3PG / AA))>

[0437] 351 parts by mass of 1,3-propylene glycol (1,3PG), 649 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added to a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator. Under a nitrogen flow, the esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less to obtain P(1,3PG / AA). The structure of P(1,3PG / AA) is shown in formula (18).

[0438]

[0439] (In formula (18), a represents a positive integer.)

[0440] The evaluation results of biodegradability showed that the biodegradability in the seawater was 47%, the biodegradability in the fresh water was 49%, the biodegradability in the soil was 55%, and the compost degradation rate was 68%. The number average molecular weight Mn was 5540, and the weight average molecular weight Mw was 24500.

[0441] (Synthesis Example 11)

[0442] <Synthesis of poly(1,4-butylene glycol / adipic acid) (P(1,4BG / AA))>

[0443] Into a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, 391 parts by mass of 1,4-butanediol (1,4BG), 609 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added, and an esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C under a nitrogen flow. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less to obtain P(1,4BG / AA). The structure of P(1,4BG / AA) is shown in formula (19).

[0444]

[0445] (In formula (19), a represents a positive integer.)

[0446] The evaluation results of biodegradability showed that the biodegradability in the seawater was 61%, the biodegradability in the fresh water was 62%, the biodegradability in the soil was 68%, and the compost degradation rate was 78%. The number average molecular weight Mn was 27,200, and the weight average molecular weight Mw was 132,000.

[0447] (Synthesis Example 12)

[0448] <Synthesis of poly(1,5-pentanediol / adipic acid) (P(1,5PG / AA))>

[0449] Into a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, 426 parts by mass of 1,5-pentanediol (1,5PG), 574 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added, and an esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C under a nitrogen flow. The reaction was terminated when the acid value of the reaction liquid became less than 2 mgKOH / g to obtain P(1,5PG / AA). The structure of P(1,5PG / AA) is shown in formula (20).

[0450]

[0451] (In formula (20), a represents a positive integer.)

[0452] The evaluation results of biodegradability showed that the biodegradability in the seawater was 63%, the biodegradability in the fresh water was 65%, the biodegradability in the soil was 67%, and the compost degradation rate was 76%. The number average molecular weight Mn was 6210, and the weight average molecular weight Mw was 26900.

[0453] (Synthesis Example 13)

[0454] <Synthesis of poly(1,6-hexanediol / adipic acid) (P(1,6HD / AA))>

[0455] Into a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, 458 parts by mass of 1,6-hexanediol (1,6HD), 542 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added, and an esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C under a nitrogen flow. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less to obtain P(1,6HD / AA). The structure of P(1,6HD / AA) is shown in Formula (21).

[0456]

[0457] (In formula (21), a represents a positive integer.)

[0458] The evaluation results of biodegradability showed that the biodegradability in the seawater was 55%, the biodegradability in the fresh water was 54%, the biodegradability in the soil was 62%, and the compost degradation rate was 68%. The number average molecular weight Mn was 9634, and the weight average molecular weight Mw was 30394.

[0459] (Synthesis Example 14)

[0460] <Synthesis of poly(1,9-nonanediol / adipic acid) (P(1,9ND / AA))>

[0461] Into a polyester reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, 535 parts by mass of 1,9-nonanediol (1,9ND), 465 parts by mass of adipic acid (AA), and 0.1 parts by mass of tetraisopropyl titanate (TIPT) were added, and an esterification reaction was carried out while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C under a nitrogen flow. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less to obtain P(1,9ND / AA). The structure of P(1,9ND / AA) is shown in formula (22).

[0462]

[0463] (In formula (22), a represents a positive integer.)

[0464] The evaluation results of biodegradability showed that the biodegradability in seawater was 58%, the biodegradability in fresh water was 57%, the biodegradability in soil was 65%, and the compost degradation rate was 75%. The number average molecular weight Mn was 4410, and the weight average molecular weight Mw was 28900.

[0465] (Example 1)

[0466] Into a glass container equipped with a stirrer and a nitrogen inlet pipe, 57 parts by mass of P(2MPD / AA) obtained in Synthesis Example 1, 443 parts by mass of P(BG / SA) obtained in Synthesis Example 2, and 0.05 parts by mass of tetraisopropyl titanate (TIPT) were added, and the container temperature was maintained at 200° C. for 3 hours under a nitrogen flow to obtain a copolyester resin containing 2MPD / AA and BG / SA as structural units. The structure of the obtained copolyester resin is shown in Formula (A-1).

[0467]

[0468] (In formula (A-1), o, p, and q each independently represent a positive integer.)

[0469] The evaluation result of the average chain length showed that the 2MPD / AA average chain length was 6.9.

[0470] The results of the biodegradability evaluation showed that the degradation rate in seawater was 16% and the degradation rate in compost was 62%.

[0471] The evaluation results of biodegradability are shown in the following Table 1 (Table 1A, Table 1B).

[0472] (Examples 2 to 6)

[0473] A copolyester resin was obtained in the same manner as in Example 1 except that the amounts of P(2MPD / AA) and P(BG / SA) and the maintenance time as the reaction time were changed to the values ​​shown in Table 1.

[0474] (Example 7)

[0475] 305 parts by mass of P(BG / SA) obtained in Synthesis Example 2, 195 parts by mass of P(2MPD / SebA) obtained in Synthesis Example 3, and 0.05 parts by mass of tetraisopropyl titanate (TIPT) were added as raw materials, and the reaction time was changed to the value described in Table 1. The same procedure as in Example 1 was performed to obtain a copolyester resin. The structure of the obtained copolyester resin is shown in Formula (A-2).

[0476]

[0477] (In formula (A-2), o, p, and q each independently represent a positive integer.)

[0478] (Example 8)

[0479] 319 parts by mass of P(BG / SA) obtained in Synthesis Example 2, 181 parts by mass of P(3MPD / AA) obtained in Synthesis Example 4, and 0.05 parts by mass of tetraisopropyl titanate (TIPT) were added as raw materials, and the reaction time was changed to the value described in Table 1. The same method as in Example 1 was used to obtain a copolyester resin. The structure of the obtained copolyester resin is shown in Formula (A-3).

[0480]

[0481] (In formula (A-3), o, p, and q each independently represent a positive integer.)

[0482] (Example 9)

[0483] 104 parts by mass of P(2MPD / AA) obtained in Synthesis Example 1, 390 parts by mass of P(BG / AA / tPA) obtained in Synthesis Example 5, and 0.05 parts by mass of tetraisopropyl titanate (TIPT) were added as raw materials, and the reaction time was changed to the value shown in Table 1. The same procedure as in Example 1 was performed to obtain a copolyester resin. The structure of the obtained copolyester resin is shown in Formula (A-4).

[0484]

[0485] (In formula (A-4), o, p, q and r each independently represent a positive integer.)

[0486] (Example 10)

[0487] 500 parts by mass of P(2MPD / AA / BG / SA) obtained in Example 5 was added to a four-necked flask equipped with a thermometer, a stirrer, a nitrogen inlet, and a reflux condenser, and dissolved in 300 parts by mass of ethyl acetate to obtain an ethyl acetate solution of a polyester polyol. 0.1 parts by mass of dibutyltin dilaurate (DBTDL) and 13 parts by mass of isophorone diisocyanate (IPDI) were added to the above solution, and the reaction was carried out while maintaining 70 to 80° C. under a nitrogen flow. The reaction was terminated when the weight ratio of isocyanate became less than 0.05% by mass to obtain a polyester urethane polyol solution.

[0488] (Example 11)

[0489] A polyester urethane polyol solution was obtained in the same manner as in Example 10 except that 10 parts by mass of hexamethylene diisocyanate (HDI) was used as the raw material.

[0490] (Example 12)

[0491] A polyester urethane polyol solution was obtained in the same manner as in Example 10 except that 15 parts by mass of diphenylmethane diisocyanate (MDI) was used as the raw material.

[0492] (Comparative Example 1)

[0493] P(BG / SA) obtained in Synthesis Example 2 was used.

[0494] The reaction conditions and evaluation results of Examples 1 to 9 and Comparative Example 1 are summarized in Table 1. In addition, the reaction conditions and evaluation results of Examples 10 to 12 are summarized in Table 2.

[0495] [Table 1A]

[0496]

[0497] [Table 1B]

[0498]

[0499] [Table 2]

[0500]

[0501] From the above examples, it was confirmed that the copolyester resin of the present invention is excellent in thermoformability and biodegradability, particularly biodegradability.

[0502] (Synthesis Example 15)

[0503] <Synthesis of poly(caprolactone) (PCL)>

[0504] 487 parts by mass of ε-caprolactone (εCL) and 5 parts by mass of methanesulfonic acid were added to a reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a distillation pipe, and a moisture separator, and a ring-opening polymerization reaction was carried out for 5 hours while maintaining the liquid temperature of the reaction liquid at 100° C. under a nitrogen flow, thereby obtaining poly(caprolactone) (PCL). The structure of PCL is shown in formula (23).

[0505]

[0506] (In formula (23), a represents a positive integer.)

[0507] The average molecular weight was measured using the above-described method for measuring the average molecular weight. The number average molecular weight Mn was 14,630, and the weight average molecular weight Mw was 23,882.

[0508] Use the above record 1 H-NMR measurement method, determination 1 H-NMR spectrum. The results are as follows.

[0509] 1 H-NMRδ(CDCl3): 1.30-1.38(m, 2H), 1.57-1.64(m, 4H), 2.26(t, 2H), 4.01(t, 2H)

[0510] As a result of the evaluation of biodegradability, the biodegradation degree in the seawater was 78%, the biodegradation degree in the fresh water was 77%, the biodegradation degree in the soil was 79%, and the compost degradation rate was 83%.

[0511] <Capa6400(Ingevity, PCL product)>

[0512] The evaluation results of the average molecular weight were as follows: the number average molecular weight Mn was 24400, and the weight average molecular weight Mw was 87757. The evaluation results of the biodegradability were as follows: the biodegradability in the seawater was 76%, the biodegradability in the fresh water was 77%, the biodegradability in the soil was 78%, and the compost degradation rate was 81%.

[0513] <BioPBS (Mitsubishi Chemical, Product P(BG / SA))>

[0514] The evaluation results of the average molecular weight were as follows: the number average molecular weight Mn was 59499, and the weight average molecular weight Mw was 171333. The evaluation results of the biodegradability were as follows: the biodegradability in the aforementioned seawater was 2%, the biodegradability in the aforementioned fresh water was 1%, the biodegradability in the aforementioned soil was 6%, and the compost degradation rate was 12%.

[0515] <Ecoflex(BASF, Product P(BG / AA / tPA))>

[0516] The evaluation results of the average molecular weight were as follows: the number average molecular weight Mn was 26445, and the weight average molecular weight Mw was 81430. The evaluation results of the biodegradability were as follows: the biodegradability in the aforementioned seawater was 1%, the biodegradability in the aforementioned fresh water was 1%, the biodegradability in the aforementioned soil was 6%, and the compost degradation rate was 10%.

[0517] (Example 13)

[0518] 5.4 parts by mass of Capa6400 (Ingevity, product PCL), 400 parts by mass of BioPBS (Mitsubishi Chemical, product P (BG / SA)), and 0.08 parts by mass of tetraisopropyl titanate (TIPT) were added to a glass container equipped with a stirrer and a nitrogen inlet tube, and the container temperature was maintained at 200° C. for 6 hours under reduced pressure to obtain a copolyester containing PCL and BG / SA as structural units. The structure of the obtained copolyester is shown in formula (B-1).

[0519]

[0520] (In formula (B-1), o, p, and q each independently represent a positive integer.)

[0521] The average chain length of the structural unit (6HH-U) derived from 6-hydroxyhexanoic acid (6HH) constituting PCL was calculated by the method described above as the average chain length of the biodegradable segment (X). In addition, the biodegradability was evaluated and the average molecular weight was measured.

[0522] These results are shown in the following Table 3 (Table 3A, Table 3B).

[0523] (Example 14)

[0524] 11 parts by mass of PCL obtained in Synthesis Example 15, 400 parts by mass of P(BG / SA) obtained in Synthesis Example 2, and 0.08 parts by mass of tetraisopropyl titanate (TIPT) were added to a glass container equipped with a stirrer and a nitrogen inlet pipe, and the container temperature was maintained at 200° C. for 3 hours under a nitrogen flow to obtain a copolyester containing PCL and BG / SA as structural units. The structure of the obtained copolyester is shown in Formula (B-2).

[0525]

[0526] (In formula (B-2), o, p, and q each independently represent a positive integer.)

[0527] The same method as in Example 13 was used to calculate the average chain length, evaluate the biodegradability, and measure the average molecular weight.

[0528] These results are shown in Table 3.

[0529] (Examples 15, 17, 18, 20 to 22)

[0530] A copolyester was obtained in the same manner as in Example 14 except that the amounts of PCL and P(BG / SA) blended and the retention time as the reaction time were changed to the values ​​shown in Table 3.

[0531] The same evaluation as in Example 13 was performed. The results are shown in Table 3.

[0532] (Examples 16, 19, 23)

[0533] A copolyester was obtained in the same manner as in Example 13 except that the amounts of PCL and P(BG / SA) blended and the retention time as the reaction time were changed to the values ​​shown in Table 3.

[0534] The same evaluation as in Example 13 was performed. The results are shown in Table 3.

[0535] (Example 24)

[0536] In a glass container equipped with a stirrer and a nitrogen inlet pipe, 197 parts by mass of Capa6400 (Ingevity, product PCL), 300 parts by mass of BioPBS (Mitsubishi Chemical, product P (BG / SA)), and 0.09 parts by mass of tetraisopropyl titanate (TIPT) were added, and the container temperature was maintained at 200° C. for 5 hours under a nitrogen flow to obtain a copolyester containing PCL and BG / SA as structural units. The structure of the obtained copolyester is shown in formula (B-3).

[0537]

[0538] (In formula (B-3), o, p, and q each independently represent a positive integer.)

[0539] The same evaluation as in Example 13 was performed. The results are shown in Table 3.

[0540] (Example 25)

[0541] A copolyester was obtained in the same manner as in Example 13 except that 52 parts by mass of Capa6400 (Ingevity, product PCL), 351 parts by mass of Ecoflex (BASF, product P (BG / AA / tPA)) and 0.08 parts by mass of tetraisopropyl titanate (TIPT) were used as raw materials. The structure of the obtained copolyester is shown in Formula (B-4).

[0542]

[0543] (In formula (B-4), o, p, q and r each independently represent a positive integer.)

[0544] The same evaluation as in Example 13 was performed. The results are shown in Table 3.

[0545] [Table 3A]

[0546]

[0547] [Table 3B]

[0548]

[0549] From the above examples, it was confirmed that the copolyester resin of the present invention is excellent in thermoformability and biodegradability, particularly biodegradability.

Claims

1. A copolyester resin, which is composed of a biodegradable segment (X) and a non-biodegradable segment (Y), wherein the biodegradable segment (X) is a structural unit showing biodegradability, and the non-biodegradable segment (Y) is a structural unit having non-biodegradability.

2. The copolyester resin according to claim 1, wherein The molar ratio (X / Y) of the biodegradable segment (X) to the non-biodegradable segment (Y) is 1 / 99 to 95 / 5.

3. The copolyester resin according to claim 1, wherein The biodegradable segment (X) is a biodegradable segment (X) derived from a polymer (x), wherein the polymer (x) contains a biodegradable structural unit derived from a hydroxyalkanoic acid or a structure in which a dibasic acid (Ia) and a diol (Ib) are bonded.

4. The copolyester resin according to claim 1, wherein The non-biodegradable segment (Y) is a non-biodegradable segment (Y) derived from a polymer (y), and the polymer (y) contains a structural unit having non-biodegradability.

5. The copolyester resin according to claim 1, wherein The average chain length of the biodegradable segments (X) is greater than 1.

2.

6. The copolyester resin according to claim 3, wherein The hydroxyalkanoic acid is a structural unit derived from 6-hydroxycaproic acid or a structural unit derived from polycaprolactone.

7. The copolyester resin according to claim 3, wherein The dibasic acid (Ia) is represented by formula (1), and the diol (Ib) is represented by formula (2), In formula (1), n ​​represents an integer of 4 to 8, In formula (2), A represents a carbon atom or an oxygen atom, R1 represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a hydroxyl group, R2 represents a hydrogen atom or a hydroxyl group, l and m are each independently an integer of 0 to 4, and l+m represents 1 or more, When A is an oxygen atom, R1 and H bonded to A do not exist. In addition, either R1 or R2 is a hydroxyl group, but R1 and R2 are not both hydroxyl groups.

8. The copolyester resin according to claim 3, wherein The biodegradable structural unit in the polymer (x) is represented by the following formula (3A) or the following formula (3B), In formula (3A) and formula (3B), R3 represents a hydrogen atom or a methyl group, l and m are each independently an integer of 0 to 4, l+m is 1 or more, and n represents an integer of 4 to 8.

9. The copolyester resin according to claim 3, wherein The dibasic acid (Ia) is at least one selected from the group consisting of adipic acid, azelaic acid, and sebacic acid.

10. The copolyester resin according to claim 3, wherein The diol (Ib) is at least one selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol and 1,9-nonanediol.

11. The copolyester resin according to claim 3, wherein The structural unit exhibiting biodegradability in the polymer (x) is at least one selected from the group consisting of the following structural units: A structural unit derived from a structure in which ethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which diethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and adipic acid are bonded, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which diethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and sebacic acid are bonded, A structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol and adipic acid are bonded together; a structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, 2-methyl-1,3-propanediol and adipic acid are bonded together; A structural unit derived from a structure in which ethylene glycol, diethylene glycol and adipic acid are bonded together; a structural unit derived from a structure in which ethylene glycol, diethylene glycol, 2-methyl-1,3-propanediol and adipic acid are bonded together; A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded together, and a structural unit derived from a structure in which ethylene glycol, 2-methyl-1,3-propanediol, adipic acid, and sebacic acid are bonded together.

12. The copolyester resin according to claim 4, wherein The non-biodegradable structural unit in the polymer (y) is derived from butylene succinate or butylene adipate / terephthalate.

13. The copolyester resin according to claim 4, wherein The non-biodegradable structural unit in the polymer (y) is: Any of a structural unit derived from a structure in which 1,4-butanediol and succinic acid are bonded together, and a structural unit derived from a structure in which 1,4-butanediol, adipic acid, and terephthalic acid are bonded together.

14. The copolyester resin according to claim 1, wherein The biodegradable structural unit, i.e., the biodegradable segment (X), comprises a unit (A) and a unit (B), wherein the unit (A) and the unit (B) are any one of the following (i) to (iii): (i) The unit (A) is a triad unit derived from "a structure formed by bonding 2-methyl-1,3-propanediol, adipic acid and 2-methyl-1,3-propanediol", and the unit (B) is a triad unit derived from "a structure formed by bonding 1,4-butanediol, adipic acid and 1,4-butanediol"; (ii) The unit (A) is a triad unit derived from "a structure formed by bonding 2-methyl-1,3-propanediol, sebacic acid and 2-methyl-1,3-propanediol", and the unit (B) is a triad unit derived from "a structure formed by bonding 1,4-butanediol, sebacic acid and 1,4-butanediol"; or (iii) The unit (A) is a triad unit derived from "a structure in which 3-methyl-1,5-pentanediol, adipic acid and 3-methyl-1,5-pentanediol are bonded together", and the unit (B) is a triad unit derived from "a structure in which 1,4-butanediol, adipic acid and 1,4-butanediol are bonded together". 15 . The copolyester resin according to claim 1 , which has a melting point (Tm) of 65° C. or higher.

16. The copolyester resin according to claim 1, wherein Copolyester resins are biodegradable in seawater, freshwater, soil and compost environments.

17. A method for producing a copolyester resin, which is a method for producing the copolyester resin according to any one of claims 1 to 16, wherein the copolyester resin comprises a biodegradable segment (X) and a non-biodegradable segment (Y). The biodegradable segment (X) is a segment derived from a polymer (x), wherein the polymer (x) contains a biodegradable structural unit. The non-biodegradable segment (Y) is a segment derived from a polymer (y), wherein the polymer (y) contains a non-biodegradable structural unit. The production method comprises the step of subjecting the polymer (x) and the polymer (y) to an ester exchange reaction to obtain a block copolymer comprising the biodegradable segment (X) and the non-biodegradable segment (Y). 18 . A resin composition comprising the copolyester resin according to claim 1 .

19. A sheet or a film formed from the resin composition according to claim 18.